Clinical applications of smart wearable sensors - Qingxiao Tao; Suwen Liu; Jingyu Zhang; Jian Jiang; Zilin Jin; Yuqiong Huang; Xin Liu; Shiying Lin; Xin Zeng; Xuemei Li; Guangming Tao; Hongxiang Chen (iScience, 2023)
Summary: Smart wearable sensors are electronic devices worn on the body that collect, process, and transmit various physiological data. Compared to traditional devices, their advantages in terms of portability and comfort have made them increasingly important in the medical field. This review takes a unique clinical physician’s standpoint, diverging from conventional sensor-type-based classifications, and provides a comprehensive overview of the diverse clinical applications of wearable sensors in recent years. In this review, we categorize these applications according to different diseases, encompassing skin diseases and injuries, cardiovascular diseases, abnormal human motion, as well as endocrine and metabolic disorders. Additionally, we discuss the challenges and perspectives hindering the development of sensors for clinical use, emphasizing the critical need for interdisciplinary collaboration between medical and engineering professionals. Overall, this review would serve as an important reference for the future direction of sensor devices in clinical use.